Levitating the future: light, magnet, and fiber unite - Chakraborty, Soumya; Wong, Gordon Kwan Leung; Oda, Ferdi; Wachter, Vanessa; Kusminskiy, Silvia Viola; Yokosawa, Tadahiro; Hübner, Sabine; Apeleo Zubiri, Benjamin; Spiecker, Erdmann; Distaso, Monica; Russell, Philip St. J.; Joly, Nicolas (Proceedings Volume PC12991, Nanophotonics X, 2024)
We report the first-ever observation of optomagnetically-driven rotation of a magnetic particle, optically levitated inside a chiral hollow-core photonic crystal fibre (HC-PCF). Rotation of the optically biaxial particle causes a change in the transmitted power and ellipticity of a linearly polarised probe beam at 632.8 nm. HC-PCF offers a versatile platform for investigating the optomechanical response of levitated magnetic particle